Effect of different doses of creatine on the bone in thirty days of supplementation in mice: FT-Raman study. Issue 5 (2011) - Miranda, Humberto; De Souza, Renato Aparecido; Tosato, Maira Gaspar; Simão, Roberto; Oliveira, Murilo Xavier; De Lima, Flávia Mafra; Ferrari, Erika; Ribeiro, Wellington; Moreira, Leonardo Marmo; Martin, Airton Abrahão
Abstract : In this study, Raman spectroscopy was employed in order to provide information about the effects of different doses of creatine on bone tissue composition of phosphate apatite (960 cm –1 ), carbonate apatite (1170 cm –1 ) representing the mineral content and collagen matrix (amide I, 1665 cm –1 ). The animals (27 Balb-C male) were divided into three groups ( n ═ per group): control (CON), supplemented with 0.5 g/kg (Cre-0.5) and with 2.0 g/kg (Cre-2.0) creatine. The experiment was carried out for thirty days. After this time, the right femur of each animal was harvested. The specimens were assessment by FT-Raman spectroscopy and in a total of 81 spectra were acquired in the medial diaphysis of the femur. The Raman data strongly suggest that only the creatine supplementation of 0.5 g/kg effective to the bone constitution. Furthermore, the present results demonstrate that creatine ingestion provokes decrease in the relative presence of carbonate in the chemical constitution of bones. The decrease in the carbonate content can be associated to a significantly bone resistance altered to several mammalians. The analysis evidenced that the mineral concentrations in the Raman spectroscopy could be a feasible method for non-invasive or minimally invasive assessment of bone tissue composition. Probably this high sensitivity can be employed to determine spectral profiles, such as wavelength of maximum absorption and maximum intensity of absorption of each wavelength, of several bone diseases.